Medialis pedis flap for reconstruction of weight bearing heel. Issue 7 (13th July 2017) - Park, Jin Sung; Lee, Jae Hoon; Lee, Jung Suk; Baek, Jong Hun
Abstract : Background: Among the various flaps available for the reconstruction of the heel, a medial plantar flap has been widely accepted as the most ideal. This flap, however, involves the medial plantar nerve and its cutaneous branches, which may lead to postoperative hyperesthesia and dual sensation. The purpose of this report was to report the outcomes of the use of the medialis pedis flap for the coverage of weight bearing heel soft tissue defect. Patients and methods: A total of 8 patients who had undergone reconstruction of the weight bearing heel with the medialis pedis flap were enrolled for this study. There were 6 male and 2 female patients and the mean age was 46 years. The causes of the defects included pressure sore, crushing injury and malignant melanoma. The mean size of the defects was 3 × 4 cm. Five cases were reconstructed with island flaps and 3 were covered with free flaps. Results: The mean size of the flaps was 3×5 cm. All flaps survived. One case developed arterial insufficiency and was treated with a vein graft. Ambulation in normal shoes was possible in all the patients. Seven cases did not report pain, but 1 case complained of mild pain. No case reported complications including pain at the donor site, ulcerations, sensory loss, hyperesthesia, or sensory disturbance. The mean follow‐up period was 14.4 months. Conclusions: The medialis pedis flap may be considered a useful flap for the reconstruction of soft tissue defects smaller than 5 cm in the weight bearing heel.